Economic Efficency Analysis of the Investment Projects in Agriculture - Briciu, Sorin; Căpușneanu, Sorinel; Bumbescu, Sorina Simona; Burdea, Raul (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
The investments represent a factor of economic growth and development on long term, and for this reason, the economic efficiency analysis of the investment projects is an important element in funding the strategic options and decisions. In this article it is realized an overview of the theoretical framework regarding the investments, the relevance of costbenefit analysis for investment projects, the economic efficiency of investments and ways to increase economic efficiency and it is realized a case study on the determination and analysis of economic efficiency of investment projects within the agriculture entities. The research leads to two major categories of tangible results, on the one hand it realized a qualitative theoretical synthesis on investments and their efficiency and on the other hand, it exemplifies the calculation, analysis and interpretation of the indicators used in the investment projects in entity by agriculture field.